A Simulation Study of the Far-Infrared Absorption Spectra of HCl Diluted in Liquid Ar. (24th September 2013) - Padilla, A.; Pérez, J.
Abstract : The far-infrared absorption coefficient of HCl diluted in liquid Ar has been calculated by using a mixed classical-quantum stochastic simulation approach. The simulated spectra have been compared with the available experimental data at different thermodynamic conditions without using ad hoc fitting parameters. Despite the fact that some discrepancies can be observed in the high frequency side of the far-infrared bands, a reasonable agreement has been found between the theoretical and the experimental spectral profiles. Both, classical and quantum simulated line shapes were comparatively analyzed, determining the time scales involved in the rotational spectra.